Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1021/jp981562w
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Reactivity of (C5H5Mg)+Complexes:  An Experimental and Theoretical Study

Abstract: The gas-phase reactivity of C5H5Mg+ complexes generated from ionized magnesocene (Cp)2Mg•+ have been investigated by means of tandem mass spectrometry. Decomposition of metastable C5H5Mg+ ions involves the metal−ligand dissociation and a hydrogen atom elimination leading to the formation of Mg+ and C5H4Mg•+ ions. Collisional activation induces further fragmentations, yielding C3H3Mg+ and C3H2Mg•+ ions. To have some insight into the structure and energetics of these four series of complexes, high-level ab initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…This is consistent with the formal description of ( c -C 5 H 5 )Mg + as ( c -C 5 H 5 ) - Mg 2+ . A very recent theoretical study of this cation indicates an interaction that is typical of an ionic bond and NBO analysis indicates a natural charge of 1.8 for Mg . Also, it is relevant to note from Figure that the measured onsets of multicollision-induced dissociation for ( c -C 5 H 5 )Mg + −RH are about 2 times higher than that for Mg + −RH, which also is consistent with electrostatic bonding with the alkane.…”
Section: Resultssupporting
confidence: 63%
“…This is consistent with the formal description of ( c -C 5 H 5 )Mg + as ( c -C 5 H 5 ) - Mg 2+ . A very recent theoretical study of this cation indicates an interaction that is typical of an ionic bond and NBO analysis indicates a natural charge of 1.8 for Mg . Also, it is relevant to note from Figure that the measured onsets of multicollision-induced dissociation for ( c -C 5 H 5 )Mg + −RH are about 2 times higher than that for Mg + −RH, which also is consistent with electrostatic bonding with the alkane.…”
Section: Resultssupporting
confidence: 63%
“…Their higher stability was explained in terms of formal Cp-Mg 2+ complexes. No binding energies of these hydrocarbon complexes were provided, but an earlier theoretical study, 23 using the natural bond order (NBO) analysis, indeed reported a rather high positive charge of 1.6e on the ligated Mg.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the energy profile can contribute to better comprehension of the dissociation channels obtained by collisional activation and tandem mass spectrometry studies. Research groups have been devoted to many works involving mass spectrometry in combination with computational chemistry. , Although the latter technique has been widely applied to gas-phase chemistry, topological analysis of the electron density by the atoms in molecules (AIM) method has been rarely used for elucidation of fragmentation mechanism. , Thus, application of parameters generated by AIM shall aid analysis of the results regarding the fragmentation mechanism.…”
Section: Introductionmentioning
confidence: 99%